Integrity monitoring of GAST-C and GAST-D simulations in low-latitude region under quiet and disturbed ionospheric activity - dos Santos Bezerra, Lucas; de Oliveira, Paulo Sérgio; Krueger, Claudia Pereira; Monico, João Francisco Galera [UNESP] (Springer Nature, 2025)
Ground-based augmentation systems (GBAS) enhance precision approach procedures by providing differential corrections from ground reference receivers, improving airborne accuracy and transmitting integrity data. This allows aircraft to calculate protection levels (PL) and ensure position error (PE) remains within acceptable bounds. However, ionospheric irregularities, particularly in low-latitude regions like Brazil, challenge GBAS efficiency, affecting availability and continuity during critical flight phases. To mitigate these disturbances, GBAS employs monitoring systems that assess integrity by tracking ionospheric conditions and other potential anomalies, ensuring computed PLs reflect the system’s ability to maintain safe operations under adverse environments. In this context, this study evaluates a simulated GBAS facility in Presidente Prudente, Brazil, using EUROCONTROL PEGASUS software to analyze the performance of GBAS approach service types C (GAST-C) and D (GAST-D) under quiet and disturbed ionospheric conditions. Results show that during periods of intense ionospheric activity, availability fell below the International Civil Aviation Organization (ICAO) threshold of 99%, with GAST-C and GAST-D achieving 94.3% and 93.5%, respectively. The study also investigated the effects of inflating the standard deviation of the vertical ionospheric gradient (σvig) to improve integrity, finding reduced occurrences of misleading information (MI) and no instances of hazardously misleading information (HMI). Availability, nevertheless, was further impacted, notably during disturbed periods. Satellite geometry and ionospheric scintillation were identified as significant factors in degrading positioning accuracy and protection levels. These findings highlight the importance of robust monitoring systems to ensure reliable GBAS operations in low-latitude regions and provide key insights for future deployment in Brazil.
Keywords: GAST-C and GAST-D; GBAS; Ionospheric disturbances; PEGASUS; System availability